2019
DOI: 10.1253/circj.cj-19-0426
|View full text |Cite
|
Sign up to set email alerts
|

The Impending Epidemic of Cardiovascular Diseases in Patients With Cancer in Japan

Abstract: of the solutions. Similarly, when oncologists assess the risk and benefit of cancer therapies, cardiologists can assist them in evaluating the risk of CVD and identifying the best therapeutic approach. Therefore, the 2 fields-cardiology and oncology-should complement each other and not act as competitors. 6 The Japanese Onco-cardiology Society was established in 2017 for better collaboration in the treatment of patients with cancer. A multidisciplinary, team-based approach is required to support the cancer tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 93 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…Cancer and CVD are closely related in terms of both scientifi c and clinical perspectives. Oncocardiology has recently gained attention by oncologists, cardiologists, and radiologists for mutual work on pathophysiology analysis and treatment strategy [1][2][3]. In various clinical settings, these specialists may collaborate in the diagnosis and treatment of cancer patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer and CVD are closely related in terms of both scientifi c and clinical perspectives. Oncocardiology has recently gained attention by oncologists, cardiologists, and radiologists for mutual work on pathophysiology analysis and treatment strategy [1][2][3]. In various clinical settings, these specialists may collaborate in the diagnosis and treatment of cancer patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of continued advances in cancer treatments, the survival rate has increased significantly. About 75% of cancer survivors suffer from one or more chronic diseases, and the leading cause of death for these survivors is CVDs (7)(8)(9). The largest cohort analysis of cancer and CVDs in China reported that 18% of patients with cancer have at least one cardiovascular risk factor and that 5% of patients with cancer have CVDs (4).…”
Section: Epidemiology: Cancer Treatments and Cvdsmentioning
confidence: 99%
“…Patients with cancer have an increased risk of cardiovascular disease including ischemic heart disease and vice versa [8][9][10][11]. A large-scale national registry including [ 6.5 million participants showed that in patients with acute myocardial infarction, 2.8% had active cancer and 6.2% had a history of cancer [25].…”
Section: Cancer and Ischemic Heart Diseasementioning
confidence: 99%
“…Heart disease and cancer are the leading causes of death worldwide especially in developed countries [5], and patients with cancer have an increased risk for cardiovascular events and mortality from shared lifestyles, risk factors, and underlying mechanisms such as inflammation, endothelial dysfunction, and oxidative stress [6][7][8][9][10][11]. Toxicities of cancer treatment, including chemotherapy and radiotherapy, also contribute to endothelial injury and vasospasm, as described in the European Society of Cardiology position paper [12].…”
Section: Introductionmentioning
confidence: 99%